Arabinogalactan enhances Mycobacterium marinum virulence by suppressing host innate immune responses - Li, Ye-yu; Liu, Han-Mei; Wang, Decheng; Lu, Yan; Ding, Cairong; Zhou, Li-Shuang; Wu, Xiang-Yang; Zhou, Zi-Wei; Xu, Shu-qin; Lin, Chen; Qin, Lian-Hua; Li, Yao; et al. (Frontiers in Immunology, 2022)
Arabinogalactan (AG) participates in forming the cell wall core of mycobacteria, a structure known as the mAGP complex. Few studies have reported the virulence of inartificial AG or its interaction with the host immune system. Using clustered regularly interspaced short palindromic repeats interference (CRISPRi) gene editing technology, conditional Mycobacterium marinum mutants were constructed with low expression of embA or glfT2 (EmbA_KD or GlfT2_KD), which are separately involved in the biosynthesis of AG arabinose and galactose domains. High-performance gel permeation chromatography and high-performance liquid chromatography (HPGPC and HPLC, respectively) assays confirmed that the EmbA_KD strain showed a remarkable decrease in AG content with fragmentary arabinose chains, and the GlfT2_KD strain displayed less reduction in content with cut-down galactose chains. Based on transmission and scanning electron microscopy (TEM and SEM, respectively) observations, the cell walls of the two mutants were found to be dramatically thickened, and the boundaries of different layers were more distinct. Phenotypes including over-secretion of extracellular substances and enhanced spreading motility with concomitant decreased resistance to ethambutol appeared in the EmbA_KD strain. EmbA_KD and GlfT2_KD strains displayed limited intracellular proliferation after infecting murine J774A.1 macrophages. The disease progression infected with the EmbA_KD or GlfT2_KD strain significantly slowed down in zebrafish/murine tail infection models as well. Through transcriptome profiling, macrophages infected by EmbA_KD/GlfT2_KD strains showed enhanced oxidative metabolism. The cell survival measured using the CCK8 assay of macrophages exposed to the EmbA_KD strain was upregulated and consistent with the pathway enrichment analysis of DEGs in terms of cell cycle/apoptosis. Overexpression of C/EBPβ and increasing secretion of proinflammatory cytokines were validated in the macrophages infected by the EmbA_KD mutant. In conclusion, AG of Mycobacterium appears to restrain host innate immune responses to enhance intracellular proliferation by interfering with oxidative metabolism and causing macrophage death. Arabinose chains of AG influence Mycobacterium virulence and pathogenicity to a greater extent.